Correction of Peri-Implant Soft Tissue Fenestration With Bony Dehiscence Associated With Intrabony Defect: A 2-Year Case Report - Sujiwan Seubbuk Sangkhamanee; Thitiwan Teparat-Burana (Case Reports in Dentistry)
Soft and hard tissue deficiencies around dental implants which can potentially compromise implant survival are commonly encountered. Complicated interventions are often required to address and resolve combinations of soft and hard tissue defects. This case report describes the management of peri-implant soft tissue fenestration accompanied by bony dehiscence associated with intrabony defect through soft tissue modification. A 51-year-old female was referred to the Periodontics and Oral Medicine Clinic with labial soft tissue fenestration at the maxillary left canine implant-supported crown. The patient complained of discomfort and malodor at the implant site. The implant showed mucosal fenestration and 6 mm probing depth (PD) with profuse bleeding at the distolabial site without mobility. A cone beam computed tomography (CBCT) demonstrated labial bony dehiscence associated with a 5.56-mm intrabony defect at mesial and distal surfaces. The implant was diagnosed as peri-implantitis with soft tissue deficiency. The treatment comprised oral hygiene instruction, debridement of the implant and all natural teeth, and mucogingival surgery with free connective tissue graft by the envelope technique. Two weeks after debridement, the mucosal margin of the implant disappeared, presenting soft tissue dehiscence of 4×4 mm. Mucogingival surgery was performed 3 weeks later. A 2-year follow-up revealed a stable mucosal margin with PD ranged 2–4 mm. In conclusion, modification of the soft tissue thickness around the implant together with excellent plaque control by the patient successfully maintained peri-implant health.